Pengelolaan Anggaran Kemenko Pmk Ri Dalam Pelaksanaan Program Bantuan Sosial Tahun 2019-2020 - Gabrieli, Fanema; Pramudiana, Ika Devi (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
This study aims to analyze the budget management of the Coordinating Ministry for Human Development and Culture of the Republic of Indonesia (Kemenko PMK RI) in the implementation of social assistance programs during the years 2019-2020. The primary focus of this research is the evaluation of effectiveness, efficiency, and transparency in budget management based on the theory of public financial management. The results of the study indicate that although there have been improvements in several aspects, such as the efficient use of funds and inter-agency coordination, there remains room for improvement in terms of transparency and evaluation mechanisms. Better and more transparent budget management is necessary to ensure that social assistance can be targeted accurately and meet the needs of communities affected by the pandemic. The research recommendations include strengthening budget planning and allocation, optimizing the use of information technology for real-time monitoring, and enhancing evaluation mechanisms and feedback from beneficiaries. By implementing these recommendations, it is expected that the budget management by Kemenko PMK RI can become more effective, efficient, and transparent, thereby supporting the goal of developing a high-quality and competitive human resource as outlined in the RPJMN 2020- 2024.